La aspiración científica disciplinar. Un mensaje de la economía a la administración (2007)
This paper collects some reflections about the scientific character of economics and about its effects on management as a related discipline. These reflections are done from a critical perspective in which the etymological aspects of what it is called the method of scientific investigation are pondered. In the final part of the paper, the importance of the management's autocritical attitude is remarked, for it adopts two streams, constructivism and humanism, as a point of departure of the deconstruction of its traditional discourse, from which economics could collect some lessons.